Forage production of Bouteloua gracilis 1986/87 (H.B.K.) Lag. ex Steud during a growing season (Semiárida, 2020)
In a plot of Bouteloua gradlis (a warm introduced grass) to the NW of Carro Quemado town, the monthly production of aereal phytomass during the growing period and its answer to nitrogenous fertilization were determined. The highest production was of '22.7,6gMS.m-2 in May /87. The percentaje of its partidpation in the total of aereal fitomass from 80 to 97% during the period analized. The response to the fertilization was good, the best results were obtained with the dose of 30 Kg N/ha in de first cut (vegetative period). In the second cut (end growing period) the best dose was the one of 90 Kg N/ha.